2004
DOI: 10.1677/joe.0.1810065
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the growth hormone receptor in an advanced teleost, the tilapia (Oreochromis mossambicus) with special reference to its distinct expression pattern in the ovary

Abstract: There is considerable evidence that the GH/IGF-I axis plays an important role in female reproduction. We report the isolation and characterization of the GH receptor (GH-R) and its gene expression profile during oogenesis in the tilapia, Oreochromis mossambicus. cDNA encoding GH-R was cloned and sequenced from the tilapia liver. The predicted GH-R preprotein consisted of 635 amino acids and contained a putative signal peptide, an extracellular region with a characteristic motif, a single transmembrane region, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(38 citation statements)
references
References 44 publications
3
35
0
Order By: Relevance
“…It is not known whether the species variation observed in mammals is also seen in teleosts. In this context, it is noteworthy to mention the results of Kajimura et al (2004) that a high plasma estradiol level did not correlate with an elevation of hepatic GHR expression in tilapia. Nonetheless, the present study is the first report demonstrating that GHR expression in fish could be regulated by both estradiol and testosterone, constituting a new target for the actions of steroid hormones on the growth axis in teleosts.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…It is not known whether the species variation observed in mammals is also seen in teleosts. In this context, it is noteworthy to mention the results of Kajimura et al (2004) that a high plasma estradiol level did not correlate with an elevation of hepatic GHR expression in tilapia. Nonetheless, the present study is the first report demonstrating that GHR expression in fish could be regulated by both estradiol and testosterone, constituting a new target for the actions of steroid hormones on the growth axis in teleosts.…”
Section: Discussionmentioning
confidence: 86%
“…3). The GHR1 clade encompasses the sequences previously reported in a number of fish species including the goldfish (Lee et al 2001), grass carp (GenBank accession number AY283778), black seabream (Tse et al 2003), gilthead seabream (CalduchGiner et al 2003), Mozambique tilapia (Kajimura et al 2004), halibut (GenBank accession number AB058418), turbot (Calduch-Giner et al 2001) and eel (isoform 1: GenBank accession number AB180476; isoform 2: GenBank accession number AB180477), as well as the Southern catfish and Nile tilapia GHR1 sequences obtained in the present study. The GHRs within this clade are structurally more homologous to GHRs found in the non-teleost vertebrates.…”
Section: Identification Of Ghr2 In Teleostsmentioning
confidence: 99%
“…According to these sequences, GHRs of other fish were isolated (CalduchGiner et al 2003;Nakao et al 2004; and other unpublished sequences in the GenBank database). A few studies showed binding of the GHR to native GH (Tse et al 2003;Kajimura et al 2004), but they did not examine interaction between the GHR and SL. Importantly, the recent studies by Fukada et al (2004Fukada et al ( , 2005 demonstrated that (1) salmonid GHR binds to GH but not to SL or PRL; (2) salmonid SLR binds more to SL than to GH or PRL; and (3) the SLR can significantly (cross-) react with GH but not with PRL.…”
Section: Phylogenetic Paradox Among Fish Slrs and Ghrsmentioning
confidence: 99%
“…Later on the GHR cDNA sequences of many species including gilthead sea bream (Sparus aurata;Calduch-Giner et al 2003), black sea bream (Acanthopagrus schlegeli; Tse et al 2003), Japanese flounder (Paralichthys olivaceus; Nakao et al 2004), common carp (Cyprinus carpio; GenBank accession number AY691176), grass carp (Ctenopharyngodon idella; AY283778), channel catfish (Ictalurus punctatus; DQ103502), Mozambique tilapia (Oreochromis mossambicus; Kajimura et al 2004), coho salmon (Oncorhynchus kisutch; AF403539, AF403540), masu salmon (Oncorhynchus masou; Fukada et al 2004), rainbow trout (Onchorhynchus mykiss; Very et al 2005), Atlantic salmon (Salmo salar; Benedet et al 2005), and Japanese eel (Anguilla japonica; Ozaki et al 2006) have been reported. Most of these GHRs share several common features, and amino acid alignments reveal a relative high degree of identity (35-40%) among GHRs of tetrapods and non-salmonid fish.…”
Section: Introductionmentioning
confidence: 99%